Emerging disease challenges to sustainable production of Brachiaria grass in Rwanda - Uzayisenga, Bellancile; Mutimura, Mupenzi; Muthomi, J.W.; Mwang’ombe, A.W.; Ghimire, Sita R. (2019)
Brachiaria grass is one of the most important tropical forages native to Africa. It is adapted to drought and low fertility soils, and known for palatability and high-quality biomass production, and thus improves livestock productivity. Due to these desirable attributes, Brachiaria grass has become increasingly popular among livestock farmers in Africa. However, the susceptibility of Brachiaria grass to diseases has been observed as an emerging challenge to the sustainable production of the grass in Africa, and current knowledge on the diseases affecting Brachiaria grass in Africa is inadequate. Therefore, this study was carried out to assess incidence, severity, and distribution of Brachiaria grass diseases in Bugesera, Huye, Nyagatare, Nyamagabe and Rwamagana districts representing five agro-ecological zones of Rwanda during the dry (July–August 2018) and wet (November 2018–January 2019) seasons. A total of 25 and 75 Brachiaria fields were surveyed in the dry and wet seasons, respectively. Disease incidence and severity were assessed on 20 stools per field from four different quadrats following established procedures. Leaf blight, rust, and leaf spot were the major Brachiaria diseases in Rwanda. The surveyed districts significantly (p < 0.001) differed in the incidence and severity of all the three diseases in both seasons. Leaf blight incidence ranged from 26% to 72% in the dry season and 24.7% to 64% in the wet season. Rust incidence ranged from 20% to 47% in the dry season and 11.3% to 47.7% in the wet season. Leaf spot incidence ranged from none to 56% in the dry season and 3.7% to 66% in the wet season. Similarly, leaf blight severity ratings ranged from 0.62 to 1.92 in the dry season and 0.37 to 1.14 in the wet season. Rust severity ratings ranged from 0.68 to 1.55 in the dry season and 0.24 to 0.86 in the wet season. Leaf spot severity ratings ranged from none to 1.85 in the dry season and 0.14 to 0.99 in the wet season. Huye, Nyamagabe and Bugesera districts had the highest incidence and severity of leaf blight, rust, and leaf spots diseases, respectively in both seasons. This study showed leaf blight, rust and leaf spots as emerging disease challenges for sustainable production of Brachiaria grass in Rwanda. This warrants immediate attention towards the development of effective management methods that are affordable to smallholder farmers in Rwanda.